INTERNET OF THINGS (IOT) –BUZZWORD FOR BUSINESS OPERATIONS - Dr.D.Ghosh (International Journal of Research Science and Management, 2015)
The high volatile business is really uncertain and quite competitive in nature. Every company wants to survive and continue to strive for higher market share. Companies are continuously trying to meet the expectations of the customers. Customers’ needs and wants are fast changing. Companies are investing heavily in creating Information Technology support and platform so as to facilitate the businesses.Thus, the domain of business is continuously changing day by day with the innovations in technology specially the Information and communication technology (ICT). Lot of interactions, transactions, operations occurs in business and due to that the businesses need different data on variety of situations-related to point of sales, users’ feedback, type of use of product, product movement and so on. Data are most important for the business managers so as to take a lot of decision related to business. The Information and communication technology revolutionized the scenario with lot of innovations. Internet of things (IoT), which means to connect the product and devices on the network of network for better access of real time data, have come up with lot of staffs. The products developed with the most innovative ways integrate with all sorts of sensing devices which captures all sorts of data. The Internet of things (IoT) provides better leverage to the firm in business.